ANALYSIS OF CLINICAL STUDY RESULTS IN PATIENTS WITH ACUTE LEUKEMIA (Modern education and development, 2024)
The study was conducted with the participation of 102 patients with acute leukemia who sought medical care at the Republican Specialized Scientific and Practical Medical Center of Hematology (RSSPMCH).To analyze clinical manifestations in patients with acute leukemia.The study was conducted with the participation of 102 patients with AL who sought medical help at the Republican specialized scientific - practical medical center of Hematology (RSSPMCH).